Risk factors of pelvic organ prolapse at Asella Teaching and Referral Hospital: Unmatched case control study - Obsa, Mohammed Suleiman; Worji, Tahir A.; Kedir, Nemo A.; Kute, Negeso G. (Frontiers in Global Women's Health, 2022)
Abstract Background Pelvic organ prolapsed (POP) is one of the sub-type of pelvic floor dysfunction (PFD) which occurs due to abnormal fall of the pelvic organs from their normal anatomic positions. Although the cause of prolapse is multifactorial, it is primarily occurs due to pregnancy and vaginal delivery. Hence, the present study was aimed to identify risk factors of pelvic organ prolapse among women who undergo Gynecological surgery. Results: A total of 147 cases and 293 controls were included in this study. Women who had history of chronic cough, previous pelvic floor surgery, constipation, vaginal tear during delivery, history of trauma, age of the women, rural resident and maternal gravidity were strongly associated with pelvic organ prolapse at P value of less than 0.05. Multigravida ((AOR 2.987 (95% CI (1.237-6.853), P=0.014), age greater than 50 years (AOR: 2.496 (95% CI 1.372-4.539), P =0.003), women with a history of pelvic floor surgery (AOR: .3.666 (95% CI 1.328-10.124), P =.012), women who had diabetes mellitus ((AOR: 4.676 (95% CI 0.908-24.075), P =0.065), and resided in rural areas ((AOR = 1.878;95%CI: .984–3.585), I2 = 47.5%, P = 0.056) were the independent predictors were of POP. Conclusions In this study, women with diabetes mellitus, previous pelvic floor surgery, rural resident, being multigravida and age greater than 40 were independent predictors of pelvic organ prolapse. Therefore, delivering health education on utilization of family planning methods, administering hormone replacement therapy for post-menopausal women with high parity and targeting intervention on all other identified risk factors were strongly recommended.